Seed point discontinuity‐based segmentation method for the substantia nigra and the red nucleus in quantitative susceptibility maps. Issue 4 (31st March 2018) - Guo, Tian; Song, Yang; Li, Jianqi; Fan, Mingxia; Yan, Xu; He, Andi; Huang, Dongya; Shen, Chaomin; Zhang, Guixu; Yang, Guang
Abstract : Background: The automatic segmentation of cerebral nuclei in the quantitative susceptibility mapping (QSM) images can provide assistance for surgical treatment and pathological mechanism studies. However, as the most frequently used segmentation method, the atlas method provides unsatisfactory results when segmenting the substantia nigra (SN) and the red nucleus (RN). Purpose: To propose and evaluate an improved automatic method based on seed points‐discontinuity for segmentations of the SN and the RN in QSM images. Study Type: Prospective. Subjects: In all, 22 subjects, 11 patients with Parkinson's disease (PD), and 11 healthy subjects (mean age of 68.0 ± 6.9 years) underwent MR scans. Field Strength/Sequence: 3T system and a 3D multiecho gradient echo sequence with monopolar readout gradient. Assessment: Manual segmentations by two radiologists (both with over 10 years of experience in neuroimaging) were used to establish a baseline for assessment. The Dice coefficient and the center‐of‐gravity distance was employed to evaluate the segmentation accuracy. Statistical Tests: The mean value and standard deviation of the Dice coefficient and center‐of‐gravity distance were calculated separately to compare segmentation results from the proposed method, the level set method, the atlas method (including the single‐atlas method and the multi‐atlas majority voting method). Results: The statistical results of Dice coefficient of the SN and the RN between the ground truth and the segmentation were 0.79 ± 0.14 and 0.77 ± 0.06 for the proposed method, 0.40 ± 0.10 and 0.65 ± 0.09 for the level set method, 0.68 ± 0.09 and 0.64 ± 0.07 for the single‐atlas method, 0.70 ± 0.06 and 0.68 ± 0.05 for the multi‐atlas majority voting method, respectively. The proposed method also provides the lowest center‐of‐gravity distance value (1.05 ± 0.71 for the SN and 0.74 ± 0.35 for the RN). Data Conclusion: The segmentation results of the proposed method performed well on the in vivo data and were closer to the manual segmentation than the atlas method. Level of Evidence: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;48:1112–1119.